Grain engineering: How nanoscale inhomogeneities can control charge collection in solar cells. (February 2017) - West, Bradley M.; Stuckelberger, Michael; Guthrey, Harvey; Chen, Lei; Lai, Barry; Maser, Jörg; Rose, Volker; Shafarman, William; Al-Jassim, Mowafak; Bertoni, Mariana I.
Abstract: Statistical and correlative analysis are increasingly important in the design and study of new materials, from semiconductors to metals. Non-destructive measurement techniques, with high spatial resolution, capable of correlating composition and/or structure with device properties, are few and far between. For the case of polycrystalline and inhomogeneous materials, the added challenge is that nanoscale resolution is in general not compatible with the large sampling areas necessary to have a statistical representation of the specimen under study. For the study of grain cores and grain boundaries in polycrystalline solar absorbers this is of particular importance since their dissimilar behavior and variability throughout the samples makes it difficult to draw conclusions and ultimately optimize the material. In this study, we present a nanoscale in-operando approach based on the multimodal utilization of synchrotron nano x-ray fluorescence and x-ray beam induced current collected for grain core and grain boundary areas and correlated pixel-by-pixel in fully operational Cu ( In ( 1 − x ) Ga x ) Se 2 solar cells. We observe that low gallium cells have grain boundaries that over perform compared to the grain cores and high gallium cells have boundaries that under perform. These results demonstrate how nanoscale correlative X-ray microscopy can guide research pathways towards grain engineering low cost, high efficiency solar cells. Abstract : Graphical abstract: Highlights: Composition variations impact charge collection in solar cells. Correlative nano-scale x-ray techniques are used to study grain boundaries. Low bandgap CIGS has beneficial grain boundary properties. Grain boundaries are detrimental in high bandgap CIGS.